Syntactic complexity of MA thesis and PhD dissertation abstracts written by native and non-native speakers of English - Ebrahimi, Seyed Foad (Tanjong Malim, 2021)
Syntactic complexity of MA thesis and PhD dissertation abstracts written by native and non-native speakers of English by Ebrahimi, Seyed Foad